DIFFERENCES IN LEARNING OUTCOMES FOR THE ONLINE AND F2F VERSIONS OF “AN INTRODUCTION TO SHAKESPEARE” - Koory, Mary Ann (Online Learning, 2003)
The same course in both an online and on-campus environment makes for an extended experimental comparison of learning outcomes, while controlling for two important variables: the instructor and the content of the course Students learn course content through four kinds of encounters—alone, one-to-one, one-to many, and many-to many. The online version of “Introduction to Shakespeare” course has consistently better learning outcomes than the on-campus version, as a result of the compelling nature of the one-to-one communication mode online and the textual nature of the many-to-many and one-to-many modes online. Text-based communication in the online class reinforces the skills pertinent to a literature class. Other crucial factors are online pedagogy and the self-selection. Ultimately, the differences between the online and F2F classrooms may be less crucial to learning outcomes than the degree to which the course design, regardless of technological environment, develops and supports students’ abilities to practice adult learning styles.